Asthma consultations in emergency departments of Peruvian health facilities during the second year of the COVID-19 pandemic - Figueroa Herrera, María Cielo (2024)
Objective: To describe the characteristics of asthma consultations provided in Peruvian emergency departments during 2021. Materials and methods: A descriptive study using secondary sources was conducted. The source of information was the open-access dataset “Morbilidad en Emergencia Hospitalaria” (Morbidity in Hospital Emergency Departments), prepared by the Ministry of Health (MINSA) and available on the Plataforma Nacional de Datos Abiertos (National Open Data Platform). A total of 4,338 consultations for patients with a definitive diagnosis of asthma treated in MINSA emergency departments were included. The evaluated characteristics were age, sex, diagnosis according to the International Classification of Diseases, Tenth Revision (ICD-10), level of care and month of consultation. In addition, patients with five or more consultations were identified to describe their emergency department use pattern, and the intensity of use for the entire sample was calculated. Descriptive statistics were performed using the free spreadsheet Jamovi 2.3.26, with absolute frequencies and percentages for the variables. Results: The consultations were predominantly concentrated in the 27 to 59 age group (56.71 %), female patients (61.80 %), the diagnosis “Asthma, unspecified” (84.21 %) and severity level I (59.78 %). An upward trend was observed from February, resulting in 560 consultations by the end of the year in December. A total of 2,988 patients had one consultation, while 41 patients had five or more consultations, with the maximum number of consultations for a single patient reaching 32. The overall intensity of use accounted for 1.25. Conclusions: In 2021, starting in February, there was an increase in the number of consultations for patients with a definitive diagnosis of asthma in MINSA emergency departments. The highest concentration of consultations was observed in the 27 to 59 age group and among female patients.